Peran historis Kosgoro - Ramadhan K. H. (Ramadhan Karta Hadimadja), 1927-; Sriwibawa, Sugiarta, 1932- (Jakarta : Pustaka Sinar Harapan, 2000)
History and role of Kosgoro, an Indonesian multi-purpose organization based on the principal of mutual cooperation in Indonesian society.
Errata slip inserted on p. 372.
Keywords: Kosgoro -- History; Cooperative societies -- Indonesia